Didactic planing in the future profesionals of the licenciatura en idioma ingles opción enseñanza in the foreing language departament at the university of El Salvador - Cárcamo Zaldaña, Brett Napoleón; Dominguez Hernández, Rosabel Sarai,; Escamilla Melgar, Ana Mirna,; Medrano López, Evelyn Arely; Rosa Campos, Zulma Karina,; Carranza Campos, Miguel Angel; Salazar Murcia, Pedro Antonio
The following research is about "Didactic planning in the future professionals of the Licenciatura en Idioma Inglés: opción Enseñanza in the Foreign Language Department at the University of El Salvador. It contains a theoretical framework in which there is information about planning and curriculum. To give more information about planning there are some sub-titles such as: lesson planning, lesson plan`s importance, the elaboration of lesson plans, lesson plan formats, etc. At the same time, in curriculum it has been mentioned the most important information according to the topic: making decisions about the design of curriculum, sources of ideas as bases of the curriculum, relating aims and objectives to curriculum foundations, etc. Information about the Major Licenciatura en Idioma Inglés, it is also presented the curricular changes that have taken place in different periods of time (1993, 1996)